22.1k views
5 votes
Select the correct answer. Rewrite the expression x^3+10x^2+13x+39/x^2+2x+1 in the form q(x)+r(x)/b(x).

Select the correct answer. Rewrite the expression x^3+10x^2+13x+39/x^2+2x+1 in the-example-1

1 Answer

0 votes

1 step: Divide the polynomial
x^3+10x^2+13x+39 by the polynomial
x^2+2x+1 with remainder:


x^3+10x^2+13x+39=(x^2+2x+1)(x+8)+(-4x+31).

Here
x+8 is quotient and
-4x+31 is remainder.

2 step: Substitute previous result into the fraction:


(x^3+10x^2+13x+39)/(x^2+2x+1)=((x^2+2x+1)(x+8)+(-4x+31))/(x^2+2x+1)=\\ \\=((x^2+2x+1)(x+8))/(x^2+2x+1)+(-4x+31)/(x^2+2x+1)=(x+8)+(-4x+31)/(x^2+2x+1).

Answer: correct choice is A.

User Yikouniao
by
5.8k points